2017
DOI: 10.1097/ico.0000000000001496
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Changes in Central Corneal Thickness During Corneal Collagen Cross-Linking, Using Isotonic Riboflavin Solutions With and Without Dextran, in the Treatment of Progressive Keratoconus

Abstract: During cross-linking, isotonic riboflavin with dextran causes a significant decrease in corneal thickness, whereas dextran-free isotonic riboflavin causes a significant increase in corneal thickness, thus facilitating the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
2
26
0
2
Order By: Relevance
“…A previous study reported a decrease in corneal thickness of 12.1% with dextran riboflavin (30 min) and a 26.1% increase pachymetry using 1.1% HPMC riboflavin (for 20 min). 23 The saturation time of riboflavin in HPMC for 20 min in the study cited above may be the cause of the most significant increase in corneal thickness when compared to our study. Kymionis et al 24 reported a 20% thickness reduction using dextran riboflavin within 30 min.…”
Section: Dovepresssupporting
confidence: 44%
“…A previous study reported a decrease in corneal thickness of 12.1% with dextran riboflavin (30 min) and a 26.1% increase pachymetry using 1.1% HPMC riboflavin (for 20 min). 23 The saturation time of riboflavin in HPMC for 20 min in the study cited above may be the cause of the most significant increase in corneal thickness when compared to our study. Kymionis et al 24 reported a 20% thickness reduction using dextran riboflavin within 30 min.…”
Section: Dovepresssupporting
confidence: 44%
“…; Zaheer et al. ). Therefore, we changed our CXL protocol to 0.1% riboflavin with methylcellulose as the main supplement (methylcellulose–riboflavin) in 2012.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the use of hypotonic riboflavin is timeconsuming and adds an extra cost to the procedure. Using methylcellulose rather than dextran in the riboflavin solution has the advantage of increasing intraoperative central corneal thickness (CCT) during CXL (Oltulu et al 2014;Zaheer et al 2018). Therefore, we changed our CXL protocol to 0.1% riboflavin with methylcellulose as the main supplement (methylcelluloseriboflavin) in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Ribo avin and Ultraviolet-A are used in cross-linking therapy [19]. Purpose in corneal cross linking; It is aimed to increase the number of cross-links in the cornea, biomechanical strength, increase in collagen ber diameter, increase in shrinkage temperature, increase enzymatic resistance, and increase resistance to edema [20,21]. At the same time corneal cross-linking and anti-collagenase effect, anterior and middle Apoptosis of keratocytes in the stroma and deep keratocytes in their follow-upit makes it reproduce again [22].…”
Section: Discussionmentioning
confidence: 99%